PATIENT FAMILIES’ EXPERIENCES IN THE INFORMED CONSENT PROCESS AT GMIM BETHESDA TOMOHON HOSPITAL: A QUALITATIVE STUDY - Walewangko, Alfriando; Adam, Arlin; Alim, Andi (HEARTY, 2025)
Informed consent is a crucial aspect of healthcare services that emphasizes effective communication between medical personnel, patients, and families, especially in high-risk medical procedures. This study aims to understand the experiences of patients’ families during the informed consent process at RSU GMIM Bethesda Tomohon, considering communication dynamics, cultural values, and medical decision-making. A qualitative case study method was used, involving in-depth interviews, observations, and documentation with families of patients who underwent informed consent for surgical procedures. The results show that communication occurs both verbally and in writing with a participatory two-way pattern. The credibility of medical staff, particularly specialist doctors, enhances family trust and acceptance of medical decisions. The collectivist cultural values of the Minahasa community play a role in decision-making through family deliberation. Empathetic, clear, and repeated communication reduces psychological barriers and improves understanding of medical risks. Families act as decision-makers, emotional supporters, and moral responsible parties for medical actions. The study recommends standardizing informed consent communication procedures based on local culture, involving responsible doctors directly in information delivery, and providing empathetic communication training for medical staff. Flexible communication policies and regular evaluations of medical communication quality are also necessary to protect patient rights and improve the quality of humane healthcare services.